Refleksi Budaya dan Pendidikan Sejarah: Implementasi Problem Based Learning dalam Meningkatkan Pembelajaran Humanis Di SMA Cilacap - Sudarto, Sudarto; Warto, Warto; Sariyatun, Sariyatun; Musadad, Akhmad Arif (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2024)
The research aims to explore how the Problem Based Learning (PBL) model can increase students' understanding and interest in history education with a humanist approach. The method used is qualitative with a case study approach, which allows researchers to delve into the experiences of students and teachers in the learning process. Data were collected through interviews, observations, and analysis of documents related to the implementation of PBL in the classroom. The results show that the application of PBL not only increases students' involvement in history learning but also enriches their understanding of relevant cultural and social contexts. This study emphasizes the importance of integrating PBL methods in history education as a way to create a more meaningful and humanist learning experience for students. The implementation of PBL in history education not only enhances humanist learning but also equips students with essential skills to face real-world challenges. However, there are various challenges faced in the implementation of PBL that must be overcome. These findings are expected to contribute to the development of the curriculum and practice of teaching history in schools.